The Role of Informal Learning in Employee Innovative Work Behaviour: Mediating Role of Transformational Leadership - Sayyam; Dr. Muhammad Tufail; Dr. Amir Ishaque; Muhammad Umair (Journal of Business & Tourism, 2021)
Long lasting learning has turned into a need for individuals’ employability and a wellspring of feasible competitive gain for organizations. Learning does not just happen through formal education but informal learning can be getting via informally. This crosssectional research demonstrated the connectionamong informal learning and employee innovative work behaviour mediated by transformational leadership. Previous studies had been done over the effect of informal learning on various outcome variables, but this study investigated to reduce the gap that employee innovative work behaviour could be confirmed by taking transformational leadership as mediating variable. A quantitative research method in shape of questionnaire survey was used to collect data from all the administrative staff (below bps-17) in four public universities of khyber pakhtunkhwa. A standardized questionnaire (adopted) was used for the collection of the required data. The gathered data was analysed through spss software to examine the mediating effect between informal learning and employee innovative work behaviour. The study found that transformational leadership has partially correlated with information learning and employee innovative work behaviour. The area for future is given at the end of the study.